Examination on self-efficacy of the pre-service teachers of classroom teacher and pre-school teacher according to creative drama method - (:unkn) unknown (ELSEVIER SCIENCE BV, 2010)
This study aims at investigating self-efficacy of the pre-service teachers of Pre-School Teacher and Classroom Teacher according to creative drama method. This search is a survey model which is quantitative search. Scale of Efficacy for Using Creative Drama Method of Can (2008) has been employed as data collection instrument. The study of validity and reliability of the scale has been carried out by Can (2008) and after making explanatory factor analysis again by researcher, the scale consisting of 46 questions has been applied on pre-service teachers of Pre-School Teacher and Classroom Teacher who study at Marmara University during the academic year of 2009 - 2010. SPSS package program has been used for analyzing and independent t test has been employed in the analysis of the data. Efficacy of the pre-service teachers has been examined according to the variables of department, class and gender; and consequently, it has been stated that there is meaningful difference in terms of department and class level, whereas there is no differentiation according to gender variable. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Creative drama; pre-service teachers; efficacy